2021
DOI: 10.1002/jgm.3305
|View full text |Cite
|
Sign up to set email alerts
|

Genetic risk score constructed from common genetic variants is associated with cardiovascular disease risk in type 2 diabetes mellitus

Abstract: Background: Patients with type 2 diabetes mellitus (T2DM) experience a twofold increased risk of cardiovascular diseases. Genome-wide association studies (GWAS) have identified T2DM susceptibility genetic variants. Interestingly, the genetic variants associated with cardiovascular disease risk in T2DM Han Chinese remain to be elucidated. The present study aimed to investigate the genetic variants associated with cardiovascular disease risk in T2DM. Methods: We performed bootstrapping, GWAS and an investigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…Here, we combined the genotype of each neonate into a genetic score to assess the effect of RBCM-associated genetic variants (ANK1, SPTA1, SPTB, SLC4A1, and EPB41) with neonatal hyperbilirubinemia. A similar method has been employed in evaluating susceptibility genes with the risk of premature coronary artery disease, prostate cancer, and systemic lupus erythematosus [12,13]. Our results confirmed that RBCM-associated gene variants have a higher frequency (40.2%, 47/117; hyperbilirubinemia cases vs. controls, p = 0.008) in neonates of hyperbilirubinemia and showed a strong association with neonatal hyperbilirubinemia risk (OR = 9.644, p = 0.006).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Here, we combined the genotype of each neonate into a genetic score to assess the effect of RBCM-associated genetic variants (ANK1, SPTA1, SPTB, SLC4A1, and EPB41) with neonatal hyperbilirubinemia. A similar method has been employed in evaluating susceptibility genes with the risk of premature coronary artery disease, prostate cancer, and systemic lupus erythematosus [12,13]. Our results confirmed that RBCM-associated gene variants have a higher frequency (40.2%, 47/117; hyperbilirubinemia cases vs. controls, p = 0.008) in neonates of hyperbilirubinemia and showed a strong association with neonatal hyperbilirubinemia risk (OR = 9.644, p = 0.006).…”
Section: Discussionsupporting
confidence: 77%
“…Odds ratios (ORs) and the 95% confidence interval were calculated for the high-risk versus the low-risk degree. The statistical methods were described previously [12,13]. All statistical analysis was carried out using SPSS 19.0, and p < 0.05 was considered as significantly different.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-four studies published PRSs of CAD that met the inclusion criteria of the scoping review (Table 4). 13,15,33–64 A reasonable degree of ancestral diversity was observed in the derived PRSs, including East Asian, Hispanic, African, and Middle Eastern. However, studies with sample populations of European ancestry were by far most common.…”
Section: Resultsmentioning
confidence: 94%
“…PRSs may predict the risk of developing specific conditions, making them valuable tools in the development of personalised medicine and risk assessments. [19][20][21][22][23] Although few studies have investigated the PRS for SLE and its association with disease manifestations or severity, [24][25][26][27] these investigations have revealed that individuals with a high PRS for SLE are more prone to severe SLE phenotypes, early onset and higher mortality. Despite the potential applications of PRSs in SLE prediction, these scores rely solely on genetic factors and do not fully consider the influence of environmental and lifestyle factors.…”
Section: Lupus Science and Medicinementioning
confidence: 99%